PROTOTYPE OF STREET LIGHT CONTROL SYSTEM USING FUZZY MAMDANI METHOD - Fadlun, Wira; Philipplus (International Journal of Engineering Technology and Natural Sciences, 2020)
Street light usually set to turn on at night based on fixed time setting. In rainy condition, it will be better that the street light turned on and the color of light is yellow instead of white for effectiveness of human sight. In this research, a system which could control the street light will be designed by considering environmental light intensity, rainy condition, and time setting. Fuzzy Mamdani method is used to adjust the level of the street light intensity. The experiment results show that the system work properly. The light intensity of the street lights can change automatically adapting the brightness of environmental light and rainy or non-rainy conditions through the fuzzy process with the highest light intensity about 248.93 (in 0-255 PWM range) with an average error between experiment results and simulation using Matlab about 0.05%. In rainy condition, the color of the street light will turn to yellow from default color (white).